Comparative Study Between Two Processes for Depolluting Waste Water from Two Wastewater Treatment Plants: Activated Sludge (Mascara) and Aerated Lagooning (Ghriss) - Bachir MAHI; Mohammed EL Amin BENDAHA; Noureddine SMAHAT; Benamar BELGHERBI (Revue Nature et Technologie)
In this work, a comparative study was carried out between two biological purification processes in a semi-arid climate: activated sludge at the plant of Mascara and aerated lagoon at the plant of Ghriss. This study was based on the analysis of the purification performances obtained through the analyses of raw and purified wastewater samples over a period of 12 months during 2021. Physico-chemical analyses were carried out for the two plants (chemical oxygen demand, biological oxygen demand, suspended matter, O2, nitrogenous materials, phosphorus materials, water temperature and pH). The variation of these parameters made it possible to determine the influence of local climatological and hydrogeological data on the purification process by activated sludge and Lagooning. Due to the high reliability of both treatment processes, both purification systems can be used as an environmentally friendly alternative.